2004
DOI: 10.1128/jb.186.7.2099-2106.2004
|View full text |Cite
|
Sign up to set email alerts
|

Restricted Distribution of the Butyrate Kinase Pathway among Butyrate-Producing Bacteria from the Human Colon

Abstract: The final steps in butyrate synthesis by anaerobic bacteria can occur via butyrate kinase and phosphotransbutyrylase or via butyryl-coenzyme A (CoA):acetate CoA-transferase. Degenerate PCR and enzymatic assays were used to assess the presence of butyrate kinase among 38 anaerobic butyrate-producing bacterial isolates from human feces that represent three different clostridial clusters (IV, XIVa, and XVI). Only four strains were found to possess detectable butyrate kinase activity. These were also the only stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
327
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 397 publications
(342 citation statements)
references
References 54 publications
14
327
1
Order By: Relevance
“…The 16S rRNA sequence of GD/7 was determined (accession number EU266552) as described before (Louis et al, 2004) and blastn analysis revealed that it was 97% identical to Coprococcus catus VPI-C6-61. A fluorescent in situ hybridisation (FISH) probe was designed for C. catus and was used to determine the abundance of this species in human volunteers (for details see Supplementary Information S1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 16S rRNA sequence of GD/7 was determined (accession number EU266552) as described before (Louis et al, 2004) and blastn analysis revealed that it was 97% identical to Coprococcus catus VPI-C6-61. A fluorescent in situ hybridisation (FISH) probe was designed for C. catus and was used to determine the abundance of this species in human volunteers (for details see Supplementary Information S1).…”
Section: Methodsmentioning
confidence: 99%
“…Bacterial isolation and cultivation Strain GD/7 was isolated on yeast extract-casitonefatty acid (YCFA) medium (Lopez-Siles et al, 2012) containing 25 mM DL lactate from a faecal sample of a 42-year-old man consuming an omnivorous diet as described previously (Louis et al, 2004). The 16S rRNA sequence of GD/7 was determined (accession number EU266552) as described before (Louis et al, 2004) and blastn analysis revealed that it was 97% identical to Coprococcus catus VPI-C6-61.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2A) in the banding profiles of the exercise group was identified and, in the bacterial species whose metabolic end-product has been revealed, showed the highest sequence similarity to the 16S rRNA gene of butyrate-producing bacterium SM7/11 and butyrate-producing bacterium T2-87 (AY305313 and AY305306 93%). 16) In respect of all 16S rRNA genes in Genbank, the highest similarity was obtained with the 16S rRNA gene of uncultured bacterial clone SWPT4 aaa04g09 (EF099822, 97%).…”
mentioning
confidence: 99%
“…Ethical approval was obtained from Grampian Research Ethics Committee (project number 00/00133). The isolations were made from roll tubes of anaerobic M2GSC medium (Miyazaki et al, 1997) or a medium designed to select for Selenomonas-like bacteria, as described previously (Louis et al, 2004). All media were prepared and maintained anaerobically using oxygen-free carbon dioxide.…”
mentioning
confidence: 99%